Ten gigabit per second optical transmissions at 1.98 µm in centimetre‐long SiGe waveguides. Issue 17 (9th August 2017) - Lamy, M.; Finot, C.; Fatome, J.; Brun, M.; Labeye, P.; Nicolleti, S.; Bogris, A.; Syvridis, D.; Ettabib, M.A.; Richardson, D.J.; Petropoulos, P.; Hammani, K.
Abstract : Error‐free transmission of 10 Gbit/s non‐return to zero optical signals along 2.5 cm long silicon germanium waveguides at a wavelength of 1.98 μm is demonstrated. Bit error rate measurements confirm the absence of penalty during the transmission through a subwavelength of 1.3 and 2.2 μm wide waveguides.